Plasma focus based flash hard X-ray source in the 100 keV region with reproducible spectrum - Raspa, Veronica Diana (2010)
A pulsed hard X-ray source with shot to shot reproducible spectrum, based on a 4.7 kJ small-chamber Mather-type plasma focus device, is presented. The hard X-ray output spectrum was measured in a single shot basis by differential absorption on metallic plates. The measured spectra have a single dominant peak around 75 keV and a spectral bandwidth covering the 40-150 keV range. A hard X-ray dose of (53±3) μGy per shot was measured on axis at 53 cm from the source, and found to be uniform within a half aperture angle of 6°. © 2010 Elsevier B.V.